2009
DOI: 10.1007/s00246-009-9609-9
|View full text |Cite
|
Sign up to set email alerts
|

Hey bHLH Factors in Cardiovascular Development

Abstract: The Notch pathway is now firmly established as a key signaling system for embryonic cardiovascular development as well as some adult pathologies in vertebrates. We have identified Hey bHLH transcriptional repressors as critical, but partly redundant transducers of these signals. Hey proteins control cardiomyocyte differentiation, epithelial to mesenchymal transition of endocardial cells, and a number of key features of arterial endothelial cells with corresponding defects in knockout mice. While most of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Interestingly, it was recently shown that reduced Hey gene expression in endocardial cells leads to impaired EMT of endocardial cells and thus defective cardiac valve formation. [25][26][27] The recent discovery that somatic cells can be first reprogrammed back to pluripotent stem cells and then driven by defined transcriptional cocktails to various cell fates 3 provides a potential avenue for autologous cardiac tissue engineering. We demonstrate here for the first time that PKD2-HDAC5-KLF signaling plays a crucial role in vertebrate AV valve formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was recently shown that reduced Hey gene expression in endocardial cells leads to impaired EMT of endocardial cells and thus defective cardiac valve formation. [25][26][27] The recent discovery that somatic cells can be first reprogrammed back to pluripotent stem cells and then driven by defined transcriptional cocktails to various cell fates 3 provides a potential avenue for autologous cardiac tissue engineering. We demonstrate here for the first time that PKD2-HDAC5-KLF signaling plays a crucial role in vertebrate AV valve formation.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] To assess whether reduced notch1b expression in bng AV endocardial cells leads to the misexpression of its downstream target genes Hey1, Hey2, and HeyL, we assayed their expression by whole-mount antisense RNA in situ hybridization and cardiac-specific quantitative real-time polymerase chain reaction. We find that hey1 and hey2 are highly expressed at the AV boundary in wild-type embryos.…”
Section: Protein Kinase D2 Controls Atrioventricular Valve Formation mentioning
confidence: 99%
“…The intracellular domain of Notch (NICD) is released and translocates into the cell nucleus, where it binds with the CSL complex, leading to activation of target genes such as the Hes/Hey family of transcription factors. [27-29] As such, expression of Hes and Hey genes is used to indicate that Notch signaling is functional in a cell. Our previous study showed that Notch receptors and ligands were expressed in HemSCs and HemECs and we were interested in determining if Notch target genes were expressed in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH signaling is a key regulatory pathway for cardiovascular development and homeostasis [1]. Its receptors mainly act through transcriptional activation of target genes by a complex of the NOTCH intracellular domain, released by gamma-secretase, the transcription factor CBF1 (RBP-Jk) and the Mastermind co-activator proteins (Maml1-3).…”
Section: Introductionmentioning
confidence: 99%